Political Communication of the Hizbut Tahrir Indonesia: A Critical Discourse Analysis - S. Sarmadan; S. Sahriadi (Journal of Indonesian Language Education and Literary, 2017)
This study aimed to describe the political communication of Hizbut Tahrir Indonesia (HTI) so that it can be understood the ideology and political attitudes of HTI organizations in the life of nation and state.The approach used was a Critical Discourse Analysis. The analysis model was critical linguistics developed by Fowler, et al.Hence, the basic analysis refered to Halliday's explanation of the structure and function of the language into the structure of grammar. In practicing the use of grammar, the vocabulary is a choice of words (diction) to know the practice of ideology.The results showed that there were 18 choices of words (diction) in political communications in an article entitled "Catatan Jubir HTI: Perjuangan HTI Bentuk Kecintaan Kepada Indonesia", namely: imperialism, bric-a-brac politics, pitting, devide et impera, separatist movement, OPM, RMS, imperialism, referendum, polling, East Timor, the unity of Indonesian territory, exploitation; hegemony; Physical colonization; Economic colonization, politics, as well as socio-cultural colonialism; problems that was wrapped around the country; and Foreign corporations. Interpretation of the political communication indicated that the HTI mass organization was a mass organization that deeply loved Indonesia. It was viewed from the use of a variety of highly pro-Indonesian HTI political language, reject imperialism and neo-imperialism, anti-disintegration, and aspire to improve Indonesian human resources in order to compete and advance in the global arena.